2017
DOI: 10.1186/s12903-017-0383-4
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of four intraoral scanners in oral implantology: a comparative in vitro study

Abstract: BackgroundUntil now, only a few studies have compared the ability of different intraoral scanners (IOS) to capture high-quality impressions in patients with dental implants. Hence, the aim of this study was to compare the trueness and precision of four IOS in a partially edentulous model (PEM) with three implants and in a fully edentulous model (FEM) with six implants.MethodsTwo gypsum models were prepared with respectively three and six implant analogues, and polyether-ether-ketone cylinders screwed on. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
375
4
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 286 publications
(437 citation statements)
references
References 42 publications
24
375
4
8
Order By: Relevance
“…Similar results were found by in 2009 by Kusek, who published a case report of a patient who was rehabilitated using a simplified surgical protocol involving laser surgery and stereolithography [39]. In the above papers, the subperiosteal implants were first fabricated by means of CAD/CAM technology (stereolithography) in epoxy resin; then, the resin implants were sent to a dental laboratory for fabrication of the cast frameworks [38, 39]. …”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Similar results were found by in 2009 by Kusek, who published a case report of a patient who was rehabilitated using a simplified surgical protocol involving laser surgery and stereolithography [39]. In the above papers, the subperiosteal implants were first fabricated by means of CAD/CAM technology (stereolithography) in epoxy resin; then, the resin implants were sent to a dental laboratory for fabrication of the cast frameworks [38, 39]. …”
Section: Discussionsupporting
confidence: 61%
“…The authors concluded that the advent of stereolithography as a new tool for modeling anatomy for subperiosteal implants and advances in computed tomography offer a higher degree of build accuracy and repeatability than was previously available [38]. Similar results were found by in 2009 by Kusek, who published a case report of a patient who was rehabilitated using a simplified surgical protocol involving laser surgery and stereolithography [39].…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Digital impressions can minimize inaccuracies such as impression material strain, displacement of implant impression components and gypsum expansion, eliminating the need for conventional impression materials and making it faster and more comfortable for patients, although the high cost of investment is still a barrier to become a standard of care . The use of IOS allows for the immediate determination of the quality of the impression, with described values of trueness ranging from 44 to 64 microns (μm) and of precision from 16 to 27 μm, depending on the IOS used but well below the currently accepted threshold of 100‐120 μm of clinical deviation, being described as a comparable alternative to conventional impression methods …”
Section: Introductionmentioning
confidence: 99%